Kreativitas Guru Pendidikan Agama Islam dalam Pemanfaatan Media Pembelajaran Berbasis Teknologi Informasi dan Komunikasi - yuniarti, yuniarti; Rozelin, Diana; Rasidin, Rasidin (Al-Miskawaih: Journal of Science Education, 2024)
This article aims to analyze the use of information and communication technology-based learning media at senior hight school 4 of Tanjung Jabung Barat Jambi. The focus of the study is how the leadership of the madrasah principal improves the quality of education personnel in this school through the use of learning media. This article comes from qualitative research with data collection using documentation, observation, and interview techniques. The results of the study indicate that the use of learning media by Islamic Religious Education teachers is adjusted to the educational material that will be delivered to students. The creativity of Islamic Religious Education teachers in the use of learning media can be seen from 4 aspects, including; fluency of thinking, flexibility of thinking, originality, and elaboration. The supporting factor for the use of learning media is the great desire of teachers and students to use learning media. While the inhibiting factor is the limited infrastructure needed. Artikel ini bertujuan menganalisis pemanfaatan media pembelajaran berbasis teknologi informasi dan komunikasi di SMAN 4 Tanjung Jabung Barat Jambi. Adapun yang menjadi fokus kajian adalah bagaimana kepemimpinan kepala madrasah dalam meningkatkan mutu tenaga kependidikan di sekolah ini melalui pemanfaatan media pembelajaran. Artikel ini berasal dari penelitian kualitatif dengan pengumpulan data menggunakan teknik dokumentasi, observasi, dan wawancara. Hasil penelitian menunjukkan bahwa pemanfaatan media pembelajaran oleh guru PAI disesuaikan dengan materi pendidikan yang akan disampaikan kepada peserta didik. Kreativitas guru PAI dalam pemanfaatan  media pembelajaran dapat dilihat dari 4 aspek, antara lain; kelancaran berpikir, keluwesan berpikir, orisinalitas, dan elaborasi. Faktor pendukung penggunaan media pembelajaran adalah besarnya keinginan guru dan peserta didik untuk memanfaatkan media pembelajaran. Sedangkan faktor penghambatnya adalah keterbatasan prasarana yang dibutuhkan.